2020
DOI: 10.1101/2020.09.25.313742
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The extracellular matrix protein agrin is essential for epicardial epithelial-to-mesenchymal transition during heart development

Abstract: During embryonic heart development, epicardial cells residing within the outer layer of the heart undergo epithelial-mesenchymal transition (EMT) and migrate into the myocardium to support and stimulate organ growth and morphogenesis. Disruption of epicardial EMT results in aberrant heart formation and embryonic lethality. Despite being an essential process during development, the regulation of epicardial EMT is poorly understood. Here we report EMT on the epicardial surface of the embryonic heart at subcellul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…What triggers these EPDCs to undergo EMT at specific developmental times and locations remains to be fully elucidated but our data suggests extracellular matrix cues are significantly involved in this process as we show an upregulation of many ECM factors implicated in cell migration, including AGRN, EGFL7, POSTN, and FN1. Just recently, studies have demonstrated agrin's critical role in regulating epicardial EMT 48 . Previous studies have also reported upregulation of POSTN and FN1 in EPDCs undergoing EMT in mice 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…What triggers these EPDCs to undergo EMT at specific developmental times and locations remains to be fully elucidated but our data suggests extracellular matrix cues are significantly involved in this process as we show an upregulation of many ECM factors implicated in cell migration, including AGRN, EGFL7, POSTN, and FN1. Just recently, studies have demonstrated agrin's critical role in regulating epicardial EMT 48 . Previous studies have also reported upregulation of POSTN and FN1 in EPDCs undergoing EMT in mice 46,47 .…”
Section: Discussionmentioning
confidence: 99%